Water is our future. the miracle in the coalfields - Gärtner, Michael R.; Bendelow, Paul (Academic Video Online, 2018)
We're witnessing the comeback of a small river and an entire landscape. For decades the Emscher in the Ruhr District was the most polluted river in Europe. Now it's being returned from an industrial sewer to a natural river system. With the help of wastewater treatment plants, liberated riverbeds, and returning animal species, a unique natural region is blossoming, one with a very distinct industrial heritage.